Prolapso de glândula de terceira pálpebra em cäes: Avaliação cito e histopatológica - Brandão, Claudia Valeria Seullner [UNESP]; Rocha, Noeme Sousa [UNESP]; Ranzani, José Joaquim Titton [UNESP]; Antunes, P. A C [UNESP]; Torelli, S. R. [UNESP] (My University, 2007)
The present experiment was carried out in ten animals with third eyelid prolapsed gland. All of the prolapsed glands were surgically excised. The age of the dogs ranged from two month to ten years old, and the breeds were Beagle (20%), Teckel (10%), Pinscher (10%), Poodle (10%) and other mongrel dogs. Aspirative citology was made in all the removed glands, after that they were fixed in 10% formalin and stained with Hematoxiline and Eosine. It was observed a focal mononuclear inflamatory infiltrate in the conjunctive and periacinal tissues. Ductal dilatation and metaplasia were noted on cells of the ducts. Cyitologic examination showed similar inflamatory infiltrate to histopatologic findings. The glands showed a chronic adenitis. The absence of histo and cytologic significance changes justify the tissue function observed during surgical excision.
Prolapsed third eyelid gland in dogs: Cytologic and histopathologic evaluation
Keywords: Dog; Histopathology; Third eyelid gland; Animalia; Canis familiaris